EVALUATION OF NITRITE AND NITRATE CONTENT IN MEAT PRODUCTS AVAILABLE ON THE MACEDONIAN MARKET - Daniela Belichovska, Aleksandra Silovska Nikolova (My University, 2024)
In recent years, there has been increasing discussion about the harmful effects of added nitrites and nitrates in processed meat products. For these reasons, consumers are increasingly focused on consuming meat products with reduced nitrite content. The aim of the present research was to determine the content of nitrites and nitrates in commercial meat products available on the Macedonian market. A total of 120 samples were analyzed, including 12 samples of dry sausages, 20 samples of boiled sausages, 20 samples of semi-dry sausages, 24 samples of meat chunk sausages, 24 samples of semi-dry cured meat products and 20 samples of dry-cured meat products. The determined content of nitrites and nitrates in the tested meat products was in accordance with legal regulations. Monitoring the levels of nitrites and nitrates in meat products is necessary to ensure safe final products on the Macedonian market.
Keywords: food safety, nitrites, nitrates, meat products